Chenodeoxycholic Acid Enhances the Effect of Sorafenib in Inhibiting HepG2 Cell Growth Through EGFR/Stat3 Pathway - Zhang, Yang; Zhang, Yan; Shi, Xiao-Jun; Li, Jun-Xiang; Wang, Lin-Heng; Xie, Chun-E; Wang, Yun-Liang (Frontiers in Oncology, 2022)
BACKGROUND: Hepatocellular carcinoma (HCC) is a highly invasive disease with a high mortality rate. Our previous study found that Chenodeoxycholic acid (CDCA) as an endogenous metabolite can enhance the antitumor effect. Sorafenib has limited overall efficacy as a first-line agent in HCC, and combined with CDCA may improve its efficacy. METHODS: HepG2 cells and Balb/c nude mice were used respectively for in vitro and in vivo experiments. Flow cytometry, Western blotting, HE and immunohistochemical staining and immunofluorescence were used to study the effects of CDCA combined with sorafenib on HepG2 cell growth and apoptosis-related proteins. Magnetic bead coupling, protein profiling and magnetic bead immunoprecipitation were used to find the targets of CDCA action. The effect of CDCA on EGFR/Stat3 signaling pathway was further verified by knocking down Stat3 and EGFR. Finally, fluorescence confocal, and molecular docking were used to study the binding site of CDCA to EGFR. RESULTS: In this study, we found that CDCA enhanced the effect of sorafenib in inhibiting the proliferation, migration and invasion of HepG2 cells. Magnetic bead immunoprecipitation and protein profiling revealed that CDCA may enhance the effect of sorafenib by affecting the EGFR/Stat3 signaling pathway. Further results from in vitro and in vivo gene knockdown experiments, confocal experiments and molecular docking showed that CDCA enhances the efficacy of sorafenib by binding to the extracellular structural domain of EGFR. Conclusion: This study reveals the mechanism that CDCA enhances the inhibitory effect of sorafenib on HepG2 cell growth in vitro and in vivo, providing a potential new combination strategy for the treatment of HCC.